ANALYSIS OF GATE TUNING ON HYBRID GRAPHENE-METAL PLASMONIC ANTENNA FOR ABSORPTION ENHANCEMENT - ULLAH, ZAKA (2021)
Innovative electromagnetic optical nanoantennas functioning at optical frequencies has turned out to be playing a vital role in the emerging field of plasmonic since these antennas have been considered as the best tools for controlling, manipulation and propagation of light. However, plasmonic antenna designs based on noble metals suffer from energy losses, and their resonance frequency is hardly tunable due to the fixed size. Additionally, their potential applications i.e., infrared sensing and imaging, have been hindered by low optical absorption. Therefore, to achieve resonance tunability and realizing unity (100%) absorption, a novel approach of hybrid graphene-metal antenna with electrostatic gating is proposed for acquiring resonance tunability in the infrared region along with the enhancement of optical absorption by employing graphene stacks where the effective coupling between graphene and metal plasmons will result in enhanced absorption.